Age-related changes in blood biochemical composition of Hu sheep - Mahmoud M. Abdelsattar; Einar Vargas-Bello-Pérez; Naifeng Zhang (Italian Journal of Animal Science, 2022)
The blood biochemical composition is indicative of the animal's performance and health status. This study evaluated the interaction between age and blood metabolites, immunoglobulins, hormones in Hu sheep. In total 30 male lambs between 1, 2, 3, 6 and 12 months (M) old were used in this study. The lambs were kept with their dams and offered the total mixed ration at 7 days of age, while at 55 days of age; the lambs were weaned and transferred to individual pens. The data were analysed using the one-way ANOVA procedure of SPSS and the Pearson’s correlation coefficient between blood parameters was calculated. The 2M old lambs had significantly lower (p < 0.05) blood biochemical parameters than 1M old lambs. However, these parameters were higher in the adult sheep except the blood glucose (GLU). In contrast, the blood albumin/globulin ratio and beta-hydroxybutyric acid (BHBA) did not show significant differences. Moreover, positive correlations were observed between blood immunoglobulins, growth hormone (GH) and insulin-like growth factor-1 (IGF-1), globulin (GLB), and blood total protein (TP). In addition, BHBA had a positive correlation with GLB and immunoglobulins. In addition, blood albumin (ALB) had a significant positive correlation with TP, GH, and IGF-1. Moreover, a significant positive correlation was between GLU and insulin. The investigation of blood biochemical parameters in sheep of different ages from 1 to 12M could be a reliable method to detect the metabolism status and health condition through the early stage of life. HIGHLIGHTS The reduction of blood metabolites, immunoglobulins, hormones at 2 M old lambs compared with 1 M old lambs due to the dietary changes from liquid to solid could challenges ruminant health. The improvements of blood biochemical profile correspond with the development of rumen and immune functions. This study may extend our knowledge about the blood biochemical profile in Hu sheep.